FEATURES OF PREDICTING THE EFFECTIVENESS OF TREATMENT OF SOFT TISSUE SARCOMAS IN ADULTS BASED ON THEIR CLINICAL PICTURE AND IMMUNOLOGICAL MICROARMAMENT. - Nasirov Saidrasul Kamalovich; Nurjabov Abbos Ikramovich; Asamedinov Nuriddin Kamolovich; Abdusattorov Oybek Kabulovich; Fayziev Farrukh Sharipovich (Scholar Express Journals, 2023)
Today there is an active increase in patients with soft tissue sarcoma. So, for example, in the Russian Federation, about 10 thousand new patients are registered annually, the incidence is 30 cases per 1 million population. The age range of incidence of soft tissue sarcoma averages 56-65 years with a peak at the age of 80-90 years. To date, it is known that the immunological microenvironment of malignant tumors varies with different localization, histological characteristics, stage, degree of differentiation, tumor ploidy [1, 2] and other factors that determine the prognosis of the disease, which makes it possible to consider the features of the tissue subpopulation composition of lymphocytes in a prognostic aspect.
Keywords: soft tissue sarcoma; prognostic factors; survival